Plasma Treatment Maintains Surface Energy of the Implant Surface and Enhances Osseointegration - Fernando P. S. Guastaldi; Daniel Yoo; Charles Marin; Ryo Jimbo; Nick Tovar; Darceny Zanetta-Barbosa; Paulo G. Coelho (International Journal of Biomaterials)
The surface energy of the implant surface has an impact on osseointegration. In this study, 2 surfaces: nonwashed resorbable blasting media (NWRBM; control) and Ar-based nonthermal plasma 30 days (Plasma 30 days; experimental), were investigated with a focus on the surface energy. The surface energy was characterized by the Owens-Wendt-Rabel-Kaelble method and the chemistry by X-ray photoelectron spectroscopy (XPS). Five adult beagle dogs received 8 implants (n=2 per surface, per tibia). After 2 weeks, the animals were euthanized, and half of the implants (n=20) were removal torqued and the other half were histologically processed (n=20). The bone-to-implant contact (BIC) and bone area fraction occupancy (BAFO) were evaluated on the histologic sections. The XPS analysis showed peaks of C, Ca, O, and P for the control and experimental surfaces. While no significant difference was observed for BIC parameter (P>0.75), a higher level for torque (P<0.02) and BAFO parameter (P<0.01) was observed for the experimental group. The surface elemental chemistry was modified by the plasma and lasted for 30 days after treatment resulting in improved biomechanical fixation and bone formation at 2 weeks compared to the control group.